(untitled) (Research, Society and Development, 2019)
The purpose of this article is to analyze the perception of the middle school mathematics teacher of a public school in relation to the use of ICT in the classroom, in order to identify the technological reality in which they are inserted. In this research we adopted a qualitative approach and to obtain the data, we conducted semistructured interviews with five teachers from a public school in Campina Grande - PB, considered as a model school. The results show that teachers recognize the potential of technologies in teaching, but that some obstacles as adequate training, computers in operation, internet, prevent them from using and inserting ICT in their pedagogical practice. In this context, we believe that the initial training is a basis for stimulating and encouraging the teacher to position himself and to request that the school and the public power provide the necessary technological resources.